PENGARUH KECERDASAN EMOSIONAL DAN GAYA BELAJAR TERHADAP LITERASI DIGITAL MAHASISWA - Putri Rahmawati; Nurul Desy Saputri; Muthiara Nur Aisah; Suparmi Suparmi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Entering the era of big data, changes are happening in all fields, including education. In this era, changes related to digital advancement continue to experience dynamics. Students are expected to be able to master digital literacy. Digital literacy includes the ability to process information. This study aims to determine the influence between emotional intelligence, learning styles, and digital literacy skills of students of the Educational Technology study program. Variables of emotional intelligence and learning style act as independent variables, as well as digital literacy as dependent variables. The subjects of this study were 106 respondents from S1 Educational Technology UNS students. Data collection was carried out by questionnaire method through Google Forms. Data processing uses the SPSS (Statistical Package for the Social Sciences) program. All instruments in this study are reliable. Based on data analysis, the results of the study show that emotional intelligence and learning style have an effect on digital literacy. This means that the variable of emotional intelligence has an effect on the digital literacy variable by 36%, while the learning style variable has an influence on digital literacy by 22.7%, and the rest is influenced by other variables outside the variables in this study.